2006
DOI: 10.3168/jds.s0022-0302(06)72250-0
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Seven Mathematical Functions in Modeling Dairy Cattle Lactation Curves Based on Test-Day Records From Varying Sample Schemes

Abstract: Daily milk yield over the course of the lactation follows a curvilinear pattern, so a suitable function is required to model this curve. In this study, 7 functions (Wood, Wilmink, Ali and Schaeffer, cubic splines, and 3 Legendre polynomials) were used to model the lactation curve at the phenotypic level, using both daily observations and data from commonly used recording schemes. The number of observations per lactation varied from 4 to 11. Several criteria based on the analysis of the real error were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 29 publications
10
106
3
3
Order By: Relevance
“…Results obtained in this study for individual lactations of standard length agree with previous reports for dairy cattle (Olori et al, 1999;Macciotta et al, 2005;Silvestre et al, 2006), with a better fit for polynomials (AS, LEG and SPL) compared with models with three parameters. No studies are currently available in the literature on fitting individual extended lactation curves.…”
Section: Resultssupporting
confidence: 90%
“…Results obtained in this study for individual lactations of standard length agree with previous reports for dairy cattle (Olori et al, 1999;Macciotta et al, 2005;Silvestre et al, 2006), with a better fit for polynomials (AS, LEG and SPL) compared with models with three parameters. No studies are currently available in the literature on fitting individual extended lactation curves.…”
Section: Resultssupporting
confidence: 90%
“…They also noticed that the occurrence of the curves without a peak arose from the peculiar combination of TD yields and their distribution along the entire lactation. Silvestre et al (2006) confirmed that the goodness of fit of lactation models depends on data availability and structure. They stated that some models such as WIL or ALI were particularly affected by the interval between tests, mostly between calving and the first TD.…”
Section: Discussionmentioning
confidence: 58%
“…At the same time, breeders expect predictions of cumulative yield with minimum error. Some researches maintain that well-fitted lactation curves may accomplish that (Olori et al, 1999;Quinn et al, 2005;Silvestre et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2006) for milk yield and Coffey et al (2002) for the traits feed intake and energy balance). Sylvestre et al (2006) hyphothesised that this function is able to fit daily data superior than functions with less than five parameters such as Wilmink (1987), Wood (1967) or Legrende polynomials of less than four degrees. Also for modelling of feed intake and energy balance amongst others, Woodford et al (1984), de Vries et al (1999 and Collard et al (2000) used the Ali and Schaeffer function.…”
Section: Model I (Fr)mentioning
confidence: 99%
“…Wood, 1967;Grossman and Koops, 1988;Kirkpatrick et al, 1994;Jamrozik and Schaeffer, 1997;van der Werf, 2001;Sylvestre et al, 2006). Ló pez- Romero and Carabañ o (2003) noted that functions frequently used for the modelling of lactation curves are those proposed by Ali and Schaeffer (1987) or Wilmink (1987).…”
Section: Model I (Fr)mentioning
confidence: 99%